2000
DOI: 10.1016/s0893-133x(99)00158-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2 Adrenergic Receptor Agonists Block Stress-Induced Reinstatement of Cocaine Seeking

Abstract: The alpha -2 adrenergic receptor agonists, clonidine, lofexidine and guanabenz, blocked stress-but not cocaineinduced reinstatement of cocaine seeking at doses that suppressed footshock-induced release of noradrenaline in prefrontal cortex and amygdala. Rats were trained to selfadminister cocaine (0.5 mg/kg/infusion, i.v; 10-12 days) and, after a drug-free period (7-13 days), were returned to the selfadministration chambers for daily extinction and reinstatement test sessions. Both intermittent footshock (15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
198
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 58 publications
20
198
1
Order By: Relevance
“…Yohimbine increases central release of noradrenaline, which previous studies have shown to play a critical role in footshock stress-induced reinstatement of drug seeking (Erb et al, 2000;Shaham et al, 2000b;Leri et al, 2002). Thus, we interpret the present data to indicate that brain noradrenaline is involved in yohimbine-induced reinstatement of palatable food seeking.…”
Section: Role Of Noradrenaline and Crf In Stress-induced Reinstatemensupporting
confidence: 76%
“…Yohimbine increases central release of noradrenaline, which previous studies have shown to play a critical role in footshock stress-induced reinstatement of drug seeking (Erb et al, 2000;Shaham et al, 2000b;Leri et al, 2002). Thus, we interpret the present data to indicate that brain noradrenaline is involved in yohimbine-induced reinstatement of palatable food seeking.…”
Section: Role Of Noradrenaline and Crf In Stress-induced Reinstatemensupporting
confidence: 76%
“…Similar to the present findings, manipulations of either the CRF or adrenergic neurotransmitter systems blocked stress-induced reinstatement and failed to alter drug-priming-induced reinstatement. The CRF antagonist D-Phe-CRF (Erb et al 1998), the alpha-2 adrenoreceptor agonists clonidine, lofexidine, and guanabenz (Erb et al 2000), as well as a mixture beta-1 and beta-2 adrenoreceptor antagonists (Leri et al 2002) were able to attenuate footshock-induced but not cocaine-induced reinstatement. It seems reasonable then that a mechanism for stress-induced reinstatement of drug-seeking behavior may involve not only the dynorphin/kappa system but also an interaction between the kappa opioid, CRF, and/or adrenergic neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, both the basolateral and central nucleus of the amygdala receive NA projections that are sensitive to stress and to adrenergic manipulations (Quirarte et al, 1998). Exposure to foot shock, for example, increases NA release in these regions (Quirarte et al, 1998;Hatfield et al, 1999;Erb et al, 2000). Also, partial 6-hydroxydopamine lesions of the ventral NA bundle projecting to the amygdala attenuate foot shock-induced reinstatement of heroin seeking (Shaham et al, 2000b), and blockade of beta-NA receptors within the central amygdala block the stress-induced reinstatement (Leri et al, 2002).…”
Section: Discussionmentioning
confidence: 99%